The Scope of Authenticity in Confession Extracted Through Reading Neurons -A Study in Iraqi Legislation- - Abdul-Ilah Al-Shaya, Fahim (Journal of Legal Studies and Researches, 2024)
This Paper Seeks to Identify Authenticity of Confession Extracted Through Using Neurons Reading Techniques. This Study Defines Some Requirements and Parameters with The Aim of Clarifying Limits of Confession Extracted Through These Techniques and Appropriately Employing Such Confession to Arrive at Fair and More Reassuring Judgments.